Good taste or gut feeling? A new method in rats shows oro‐sensory stimulation and gastric distention generate distinct and overlapping brain activation patterns. Issue 7 (15th July 2020) - Roelofs, Theresia J. M.; Luijendijk, Mieneke C. M.; van der Toorn, Annette; Camps, Guido; Smeets, Paul A. M.; Dijkhuizen, Rick M.; Adan, Roger A. H.
Abstract: Satiation is influenced by a variety of signals including gastric distention and oro‐sensory stimulation. Here we developed a high‐field (9.4 T) functional magnetic resonance imaging (fMRI) protocol to test how oro‐sensory stimulation and gastric distention, as induced with a block‐design paradigm, affect brain activation under different states of energy balance in rats. Repeated tasting of sucrose induced positive and negative fMRI responses in the ventral tegmental area and septum, respectively, and gradual neural activation in the anterior insula and the brain stem nucleus of the solitary tract (NTS), as revealed using a two‐level generalized linear model‐based analysis. These unique findings align with comparable human experiments, and are now for the first time identified in rats, thereby allowing for comparison between species. Gastric distention induced more extensive brain activation, involving the insular cortex and NTS. Our findings are largely in line with human studies that have shown that the NTS is involved in processing both visceral information and taste, and anterior insula in processing sweet taste oro‐sensory signals. Gastric distention and sucrose tasting induced responses in mesolimbic areas, to our knowledge not previously detected in humans, which may reflect the rewarding effects of a full stomach and sweet taste, thereby giving more insight into the processing of sensory signals leading to satiation. The similarities of these data to human neuroimaging data demonstrate the translational value of the approach and offer a new avenue to deepen our understanding of the process of satiation in healthy people and those with eating disorders.